Histological Findings in Infective Endocarditis—A Retrospective Cohort Study Conducted at “Dr. Carol Davila” Central Military Emergency University Hospital in Bucharest - Corina-Ioana Anton; Ion Ștefan; Sorin Duțulescu; Florica Stăniceanu; Cosmin Alexandru Buzilă; Alexia-Teodora Ștefan; Adrian Streinu-Cercel (Life)
Background: Histological findings of infective endocarditis (IEs) in mechanical valves present a complex diagnostic challenge owing to the lack of a precise definition. This ambiguity is further complicated by the natural degenerative processes that occur in the mechanical valves over time. Consequently, pathologists and clinicians face significant difficulties in distinguishing between genuine infective processes and the normal wear and tear of mechanical valves. Method: This retrospective cohort study was conducted between January 2017 and January 2024 and examined tissue samples from 93 patients who underwent a surgical removal of mechanical heart valves, with 41 cases suspected of infective endocarditis and 52 cases of non-IE. The researchers aimed to establish more precise histological criteria for distinguishing between these two conditions, focusing on two key features: vegetations and inflammatory patterns. Results: IE in patients with prosthetic heart valves presents distinct histological features that aid in the diagnosis and differentiation of non-infective complications. Hallmark characteristics include vegetation and inflammatory infiltrates with neutrophils. Valve tissue specimens from patients whose mechanical valves were removed because of non-infectious complications showed a different histological profile. Inflammatory infiltrates were observed in approximately 26% of these cases; however, they were primarily composed of macrophages and lymphocytes rather than neutrophils. Conclusions: By emphasizing neutrophil-rich inflammation as a key indicator, clinicians and pathologists could more effectively distinguish between true infective endocarditis and non-IE that can occur in the mechanical valves. This distinction is crucial for appropriate patient management as the treatment strategies for infective and non-infective valve conditions differ significantly.